Effects of Video Modeling for Young Adults With Autism in Community Employment Settings. (November 2020) - Bross, Leslie Ann; Travers, Jason C.; Wills, Howard P.; Huffman, Jonathan M.; Watson, Emma K.; Morningstar, Mary E.; Boyd, Brian A.
This single case design study evaluated the effects of a video modeling (VM) intervention on the customer service skills of five young adults with autism spectrum disorder (ASD). Verbalization of greeting, service, and closing phrases contextualized to community employment settings were the target behaviors. A systematic approach to visual analysis indicated the presence of a functional relation for all participants. Coworkers, job coaches, and supervisors successfully applied the VM intervention during the generalization condition. Maintenance probes conducted at 2 and 4 weeks indicated that most customer service skills were maintained. Results indicated VM was also effective in enhancing the quality of interactions with customers. Implications for research and practice related to the competitive employment of young adults with ASD are discussed.